Rasionalitas Epistemik dalam Pengambilan Keputusan Pemasaran dan Dampaknya terhadap Kinerja Pemasaran Berkelanjutan UMKM - Tarso; Koswara, Asep; Budiarti, Isniar; Rahayu, Siti Kurnia; Sulistyo, Dedi (Jurnal Bisnis Administrasi dan Manajemen, 2026)
This study aims to analyze the influence of epistemic rationality in marketing decision-making on sustainable marketing performance among MSMEs in Kalasan District, Sleman. Using a quantitative approach with a correlational-explanatory design, this research examines causal relationships through a microfoundations perspective. Primary data were collected via Likert-scale questionnaires from 384 MSME owners or managers selected using purposive sampling. Data analysis was performed using simple linear regression with SPSS version 30 software. The results indicate that epistemic rationality has a positive and significant effect on sustainable marketing performance, with a coefficient of determination (R2) of 0.38. These findings confirm that the quality of cognitive processes, specifically the ability to evaluate evidence and justify knowledge, is a crucial determinant of long-term marketing success. Theoretically, this study strengthens the literature on the role of individual cognitive factors in explaining organizational performance. Practically, these results imply the importance of enhancing information literacy and critical reasoning for MSME actors to mitigate decision biases amidst high market uncertainty.